Literasi Digital Bagi Pelaku UMKM Sebagai Sarana Meningkatkan Pembangunan Kelurahan Jatirahayu - Hiswara, Abrar; Hidayat, Aldi Sandi; Prasetya, Rayhan Daffa; Malik, Raihan; Tua, Situmorang Ondo Palito; Damayanti, Risma; Alfarizi , Rafi Azhar; Afif, Aban Abyan; Akbar, Catur Rizky Nur; Alkahfi, Arfi; Wardhana, Erlangga Respaty (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The advancement of information technology in the digital era has significantly impacted various aspects of life, including the economic and social sectors. However, the digital literacy level of the Jatirahayu community remains moderate, as reflected in their limited understanding of safe internet use and SME digitalization. The lack of awareness regarding digital security and the minimal utilization of digital platforms by SME entrepreneurs are the main challenges in this area. This Community Service Program (PkM) aims to enhance digital literacy among the community, particularly in internet security and ethics, while assisting SME digitalization by registering business locations on Google Maps. The implementation methods include initial surveys, coordination with local authorities, material preparation, invitation distribution, and conducting socialization sessions along with technical assistance for SMEs. The results indicate that the internet literacy workshop successfully raised awareness about information validation, personal data protection, and online fraud detection. Additionally, the SME digitalization program helped business owners understand the benefits of digital platforms and successfully register several businesses on Google Maps. The evaluation of program effectiveness revealed that most participants gained a better understanding of digital literacy, although further follow-up is needed for sustainable implementation. In conclusion, this program effectively increased community awareness of safe internet usage and positively impacted SME digitalization. Moving forward, further collaboration with local government and additional training will be essential to ensure optimal technology utilization for the Jatirahayu community.